Pendampingan Dan Pengembangan UMKM Zahra Woody Craft Di Kelurahan Blitar Melalui Strategi Branding - Ariyani Dewi Safitri; Sugeng Purwanto (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Micro, Small and Medium Enterprises (MSMEs) are business activities carried out by individuals or groups that aim to prosper individuals and groups. However, of the large number of existing MSMEs, MSMEs actors usually only focus on selling points without paying attention to the branding of their products. The purpose of this service is to increase the selling value of MSMEs products by adding value with a branding strategy. Branding is one way that can be done as a solution to marketing problems that are often faced by MSMEs and also as a marketing strategy. One example of MSMEs that need a branding strategy is Zahra Woody Craft's MSMEs. The method used in this community service activity is divided into three stages, namely the survey stage, the training stage and the application of branding, and the maintenance and evaluation stage. This branding assistance is also carried out so that Zahra Woody Craft SME products can compete in the market, and can increase the profits generated.opportunities and take advantage of their advantages.